Zinc-based composites with enhanced mechanical and tribological properties by in-situ formed ceramic particles - Kumar V.; Gautam G.; Sharma S.; Mohan A.; Mohan S. (My University, 2025)
In this study, an innovative approach was undertaken to develop zinc-based composites that exhibit enhanced mechanical and tribological properties by integrating in-situ generated ZrB2 particles. The evaluation of the newly developed alloy and composites involved comprehensive analysis of optical microscopy (OM), X-ray diffraction (XRD), scanning electron microscopy (SEM), as well as rigorous mechanical and tribological testing. The OM and SEM show a homogeneous dispersion of the in-situ formed ZrB2 ceramic particles within the zinc-aluminum (Zn-Al) matrix, indicating successful reinforcement incorporation. The XRD analysis confirmed the existence of ZrB2 peaks in the composite, verifying the formation of the ZrB2 reinforcement. Mechanical behavior including hardness, tensile strength, and compressive strength was also compared with the pure zinc-aluminum matrix. The composite exhibited significantly improved mechanical properties, highlighting the beneficial effects of the in-situ formed ZrB2 particles on the overall composite performance. Furthermore, the tribological testing result indicates that the incorporation of ZrB2 resulted in a substantial decline in wear rate to the pure zinc-aluminum matrix, demonstrating the enhanced tribological characteristics of the composites. A comprehensive study of the present composite provides valuable insights into the performance of these composites, making them suitable for various demanding applications. © 2024 selection and editorial matter, Saumya Shah, Hemant Nautiyal, Gaurav Gugliani, Ashwani Kumar, Tanuj Namboodri and Yogesh Kumar Singla; individual chapters, the contributors.